PENGARUH PERCEIVED SERVICE QUALITY TERHADAP REPURCHASE DAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING PADA FAST FOOD RESTAURANT DI SURABAYA - Jocellynne Saintz (Jurnal Manajemen Pemasaran, 2018)
The purpose of this research aims to analyze the effects of Perceived Service Quality towards Repurchase with Customer Satisfaction as an intervening variabel  inFast food restaurant. This research was conducted by distributing questionnaires to 100 respondents who were customers of Fast food restaurants who had made transactions in the last six month. This research use the Perceived service quality (X1) variable with the indicators Reliability, Responsiveness, Assurance, Empathy, Tangible, Customer satisfaction variable (Y1) with the indicators Fulfillment, Pleasure, Ambivalance, Repurchase variable (Z1) with the indicators Interest, Pleasure-based value, Sign value, Risk Pribability, dan Risk. The results show: (1) Perceived service quality influence significantly effect customer satisfaction; (2) Perceived service quality affect significantly effect repurchase; (3) customer satisfaction has a significant impact on repurchase